BAD NEWS ANNOUNCEMENT ON INVESTOR’S MONDAY IRRATIONALITY: INSIGHT FROM MALAYSIA - Rayenda Brahmana; Chee-Wooi Hooy; Zamri Ahmad (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
The lack of empirical dossiers on the examination of the weekend effect causes intrigues us to investigate its determinant in the trading behaviour perspective. Employingone traditional interaction dummy model, and one day-by-day model, we found the market index and size-based portfolios of weekend effect have been driven by the attention of investor. Further, under the attention bias hypothesis, we confirm that investor’s irrationality during Monday is the driver of the anomaly because of its heuristical bias judgment. We address the difficulties that investors face on searching the thousands of stocks they can potentially deal on the first trading day as the rationalization. In a short, our findings surmise that attention bias is the driver of investor irrationality on Monday and resulting Weekend Effect.Keywords: weekend anomaly, bad news, attention bias, Malaysia stock market